Seeing the fruit for the trees in Borneo - Kettle, Christopher J. (2011)
The recent mass fruiting of forest trees in Borneo is an urgent wakeup call: existing policy instruments, financial mechanisms, and forestry infrastructure are inadequate to take full advantage of these infrequent opportunities for forest restoration and conservation. Tropical forest restoration can provide substantial benefits for biodiversity conservation, climate change mitigation, and poverty alleviation. Yet the unpredictability of the synchronized flowering and consequent mass fruiting of many forest trees in Borneo presents a distinctive set of challenges for forest restoration. Significant financing and a considerable coordinated effort are required to prepare for future mass fruiting events if we are to capitalize on opportunities for ecological restoration. The continued high rate of forest clearance in this region and the rarity of mass fruiting events suggest that there may be few remaining opportunities to prevent widespread species extinctions. In this article we propose a facilitatory policy framework for forest restoration in Borneo to stimulate action in advance of the next mass fruiting of forest trees.